The Association between Ethical Decision-Making, Job Satisfaction, Organisational Commitment and Selected Demographic Variables (Malaysian Management Journal, 2003)
Job satisfaction and organisational commitment are variables that have been frequently studied. However, the relationship between ethical decision-making and these two variables are seldom explored. This study conducted on 200 employees from public and private companies in various parts of Kuala Lumpur, aims to investigate the relationship between these three variables. Instruments were used from Paolillo & Vitell (2002), Hunt, Wood & Chonko (1989) and Dubinsky & Hartley (1986) to measure ethics, organisational commitment and job satisfaction respectively. Results show that there is a positive correlation between ethics and organisational commitment and between job satisfaction and organisational commitment. However, contrary to expectations, there is no significant correlation between ethics and job satisfaction. The negative correlation between organisational commitment and position r = -0.288, p< 0.1 suggests that people higher up in the hierarchy are less committed towards the organisation. The absence of any significant correlation between ethics and age, experience, and position is also contrary to previous studies conducted in the West. This suggests that, unlike the West, ethics does not increase or decrease with age, experience, and position.